Development of a nearshore oscillating surge wave energy converter with variable geometry. (October 2016) - Tom, N.M.; Lawson, M.J.; Yu, Y.H.; Wright, A.D.
Abstract: This paper presents an analysis of a novel wave energy converter concept that combines an oscillating surge wave energy converter (OSWEC) with control surfaces. The control surfaces allow for a variable device geometry that enables the hydrodynamic properties to be adapted with respect to structural loading, absorption range and power-take-off capability. The device geometry is adjusted on a sea state-to-sea state time scale and combined with wave-to-wave manipulation of the power take-off (PTO) to provide greater control over the capture efficiency, capacity factor, and design loads. This work begins with a sensitivity study of the hydrodynamic coefficients with respect to device width, support structure thickness, and geometry. A linear frequency domain analysis is used to evaluate device performance in terms of absorbed power, foundation loads, and PTO torque. Previous OSWEC studies included nonlinear hydrodynamics, in response a nonlinear model that includes a quadratic viscous damping torque that was linearized via the Lorentz linearization. Inclusion of the quadratic viscous torque led to construction of an optimization problem that incorporated motion and PTO constraints. Results from this study found that, when transitioning from moderate-to-large sea states the novel OSWEC was capable of reducing structural loads while providing a near constant power output. Highlights: Introduces an oscillating surge wave energy converter with active control surfaces. Control surfaces allow tuning of device hydrodynamics to meet design goals. Sensitivity of hydrodynamic coefficients to device size and geometry are explored. Active structure can tune absorbed power, foundation loads, and power-take-off torque. Base power maintained while shedding loads through geometric changes to structure.